(untitled) (Portuguese Journal of Family Medicine and General Practice, 2015)
Introduction: Many survivors of polio develop complications after a period of clinical stability. This case report demonstrates the need for the family physician to become familiar with the multiple facets of the late effects of polio and to recognize them as a disease entity. Description of the case: A 69 year-old woman had polio with sequelae. Her life story showed how the struggle to overcome deficiency was central to her trajectory. Decades after the onset of the acute disease, she presented with progressive complaints of muscle weakness, fatigue, myalgia, polyarthralgia, tingling of her hands, and depression. This caused increasing functional disability, intolerance to cold, urinary incontinence, sleep disturbance, and fasciculation. Physical examination and diagnostic tests showed chronic nerve injury in the lower limbs, carpal tunnel syndrome, and various musculoskeletal disorders. Faced with new symptoms, old feelings associated with disability that she felt she had overcome, were awakened. The treatment plan involved a multidisciplinary team. It included control of symptoms and disease progression, treating coexisting psychopathology, promotion of a healthy lifestyle, changes in her housing, prescription of assistive devices, combating isolation, mobilization of informal resources, health and social services, and transmission of information about the disease and related problems. Comment: The late effects of polio can be minimized by following suggested guidelines. Effective management requires a doctor who can identify the characteristic cluster of signs and symptoms and their psychosocial effects and formulate an individualized treatment plan.